Uncovering neurodevelopmental features in bipolar affective disorder. (22nd May 2019) - Valli, Isabel; Fabbri, Chiara; Young, Allan H.
Summary: Schizophrenia and bipolar disorder are genetically related and their clinical features overlap. Schizophrenia is conceptualised as a neurodevelopmental disorder but the evidence for bipolar disorder is less clear. Cluster-analytic approaches reveal different cognitive profiles within bipolar disorder, possibly reflective of differing neurodevelopmental loads, which are also suggested by recent genetic and neuroimaging studies. Such studies suggest the potential utility of further clinical subcategories in bipolar disorder based on neurodevelopmental load. Declaration of interest: None.